Sustainability: A paradigmatic shift in entrepreneurship education - Frances M. Amatucci; Nelson Pizarro; Jay Friedlander (New England Journal of Entrepreneurship, 2013)
This article proposes that sustainability represents a paradigmatic shift from traditional perspectives in entrepreneurship education. This “call to action” argues that it is imperative for entrepreneurship scholars and practitioners to add sustainability to academic curricula and consulting support activities. The evolutionary development of entrepreneurship from the traditional profit-oriented perspective to sustainable entrepreneurship is described. A case study of an academic institution, which has successfully incorporated sustainability principles into its curriculum, is provided.This article is among the first that details the importance of a paradigmatic shift because “business as usual” is no longer effective in the twenty-first century.